LncRNA RMRP accelerates hypoxia-induced injury by targeting miR-214-5p in H9c2 cells - Yan Teng; Ming Ding; Xiaojian Wang; Hao Li; Qinyue Guo; Jinqi Yan; Lan Gao (Elsevier, 2020)
Objective: To elucidate the function of lncRNA RMRP in hypoxia-induced acute myocardial infarction (AMI) in vitro and explore its underlying mechanism. Methods: Hypoxic injury was confirmed by measurement of cell viability, LDH release, migration, invasion, and apoptosis in H9c2 cells. The interactions between RMRP and miR-214-5p as well as miR-214-5p and p53 were also investigated. Results: Hypoxia treatment significantly induced cell damage in H9c2 cells, accompanied with the up-regulation of RMRP expressions. Transfection of RMRP siRNA remarkably attenuated hypoxia-induced injury by enhancing cell viability, migration and invasion, and reducing cell apoptosis and LDH release; whereas, enforced expression of RMRP aggravated hypoxia-induced injury. Furthermore, RMRP served as an endogenous sponge for miR-214-5p, and its expression was negatively regulated by RMRP. The effects of RMRP knockdown on hypoxia-induced injury were further enhanced with miR-214-5p overexpression, but significantly abrogated with miR-214-5p silence. Moreover, p53 was verified as a direct target of miR-214-5p, and functional investigation revealed that RMRP regulated hypoxia-induced injury via modulating p53 signaling pathway, which was partially mediated by miR-214-5p. Conclusion: Our findings demonstrated the novel molecular mechanism of RMRP/miR-214-5p/p53 axis on the regulation of hypoxia-induced myocardial injury in H9c2 cells, which might provide potential therapeutic targets for AMI treatment. Keywords: Acute myocardial infarction, LncRNA RMRP, miR-214-5p, p53, Hypoxia-induced injury